The resilience of coastal marshes to hurricanes: The potential impact of excess nutrients. (May 2020) - Mo, Yu; Kearney, Michael S.; Turner, R. Eugene
Graphical abstract: Highlights: The marsh growing season was shortened by hurricanes and recovered the following year. The marsh area substantially decreased after hurricanes and rebounded in two years. The intermediate and brackish marshes in the Breton Sound Basin showed the most damage. Long-term nutrient enrichment may impair the marshes' resilience against hurricanes. Abstract: Hurricanes pose an increasing threat to coastal environments as the intensity and severity of hurricanes are predicted to increase under the changing climate. Coastal wetlands are effective nature-based defenses of coastal cities against storms. However, the ecosystems themselves are also susceptible to the impacts of hurricanes, which are highly complex and not fully understood. Here we utilize multi-decadal satellite data archives (Landsat 1984–2014 and MODIS 2005–2015) and long-term coast-wide field-based environmental data (1978–2018) to investigate the impacts of hurricanes Katrina (2005), Gustav (2008), and Isaac (2012) on the coastal marshes in Louisiana, USA, where the hurricanes made landfall. While the hurricanes had immediate impacts on the marshes' biomass and area at an ecosystem scale, general recovery was observed in the next one and two years. We also found that the most severe damage always occurred in the intermediate and brackish marshes of the Breton Sound basin, where the nitrogen concentration in the water was significantly higher compared to areas with less damage (P < 0.01). Because excess nutrient can reduce the marshes' root growth and degrade their root mat, we posit that the long-term nutrient enrichment in the area, which resulted from the diverted Mississippi River water, has increased the marshes' susceptibility to hurricanes. The results highlight the resilience of coastal marsh ecosystems against hurricanes, but also underline the profound synergistic effects of climatic and anthropogenic factors on the sustainability of coastal ecosystems, which have important implications for coastal management under the current climate trend.